Establishment of Space syntax to read and analyze urban network; the case of study, Famagusta city of Cyprus - EHSAN VALIPOUR; ABDOLLAH MOBARAKI; MOJDEH NIKOOFAM; SAMIRA TAYYEBISOUDKOLAEI (Journal of Contemporary Urban Affairs, 2019)
Architects and designers should be familiar with the city developmental process to know about all the city aspects if they are hidden the whole time. This matter shows the importance of studying the urban sections to find out the city critical points. The method is the space syntax in one view which is the consideration of urban network analysis and it would be presented by graphs and maps by a computational description of the selected places. The main target of the space syntax establishment is to study the urban network issue by clarifying the most logical routes in the urban road network. This study has the aim to implement the space syntax as a method to determine urban network problems in order to achieve new suggestions to increase the urban network integration. In this regards, Famagusta city in Cyprus is chosen to study to present the new suggestion.